STUDI DESKRIPTIF MENGENAI ZONA TOLERANSI PENGGUNA KARTU SIM CARD - Juliani Dyah Trisnawati; Ema Andajani; Budhiman Setyawan (Journal of Management and Business, 2010)
This study describes the tolerance zone for the assessment of service quality cellular phone card providers in the city of Surabaya. Variables which refer to the variables used in the variable service quality (SERVQUAL) Zeithaml, Parasuraman, and Berry (1990) which includes dimensions reliability, assurance, tangible, Empathy, and responsiveness. Furthermore, the analysis obtained questionnaires aimed to describe the MSS (Measure of Service Superiority), namely the gap between service perceptions and service desired, and MSA (Measure of Adequate Service) is the gap between service perceptions and service adequate, and the tolerance zone is the gap between desire service and adequate service. Moreover, tolerance zone is used to explore customer satisfaction to the individual transaction, or service Encounters, and customer satisfaction for services provided by mobile phone providers in the city of Surabaya as a whole.